Experimental investigation of structural failure during the cooling phase of a fire: Timber columns. (22nd October 2022) - Gernay, Thomas; Zehfuß, Jochen; Brunkhorst, Sven; Robert, Fabienne; Bamonte, Patrick; McNamee, Robert; Mohaine, Siyimane; Franssen, Jean‐Marc
Abstract: This paper describes fire tests on loaded glued laminated timber columns in which the structural response was measured during the heating and cooling phases. Identical columns with 280 × 280 mm 2 cross‐section and 3.7 m length were tested under various heating durations in a standard furnace to investigate integrity to full burnout. Two of the columns were subjected to ISO 834 heating until failure and their measured fire resistance was 55 and 58 min, respectively. Two columns were subjected to 15 min of ISO 834 heating followed by controlled cooling; these columns failed during the cooling phase, respectively after 98 and 153 min. Flame self‐extinction occurred after approximately 40 min while smoldering continued locally. Two columns tested under 10 min of ISO 834 heating both survived the defined heating–cooling exposure. Thermocouples inside the columns show sustained temperature increases for hours after the end of the heating phase. These full‐scale furnace experiments show that timber columns may fail during the cooling phase after exposure to standard heating for about 25% of the standard fire resistance duration. These results, in line with previous numerical predictions, highlight the need for further investigation into fire safety until full burnout for timber structures.